Losartan Induced ANGIO EDEMA: a RARE CASE Report - Deep Pandit; Aniket Saha; Najma Naini Ahmed; Brunda MS; Praveen Kumar; Sukamal Dey (International Journal of Allied Medical Sciences and Clinical Research, 2025)
Angioedema is a rapid, localized swelling of subcutaneous or submucosal tissues, which can be life-threatening when involving the airway. It is most often associated with angiotensin-converting enzyme inhibitors (ACEIs), while angiotensin receptor blocker (ARB)-induced angioedema is rare, with an incidence of approximately 0.1%. Losartan-related cases are uncommon, and onset can be delayed, occurring even after years of therapy. Methods We present the case of a 75-year-old male with a 15-year history of hypertension managed with losartan 50 mg daily and ecosprin 75/10 mg. :he patient was evaluated in the emergency department for acute-onset swelling of the tongue, neck, and face, along with throat itching. Clinical examination and laboratory investigations, including complete blood count and immuno-globulin E levels, were performed. Suspected offending drug was discontinued and replaced with an alternative anti-hypertensive. Supportive treatment was initiated. Results:Vital signs on presentation were stable. Laboratory parameters were within normal limits. Losartan was stopped and replaced with cilnidipine. The patient received intravenous hydrocortisone, chlorpheniramine, and betamethasone, along with supportive therapy. Significant improvement was observed within 24 hours, with complete resolution of symptoms over subsequent days. The patient was discharged in stable condition on oral antihistamines and an alternative antihypertensive regimen, with no recurrence noted during follow-up. Conclusion:Although uncommon, ARB-induced angioedema can occur unpredictably, even after prolonged use. Early recognition, immediate discontinuation of the offending agent, and supportive management are essential to prevent airway compromise. Clinician awareness and patient education regarding potential hypersensitivity reactions to ARBs remain crucial for early intervention and improved outcomes.